2016
DOI: 10.1002/jso.24302
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of colloid adenocarcinoma of the lung: A report of six cases

Abstract: On CT, CA appears a solitary solid nodule. Further, FDG-PET findings present various (18) F-FDG accumulations. Lobectomy with systematic lymph node dissection is an appropriate procedure in view of lymph node metastasis. Since the definitive diagnosis of CA of the lung is difficult, further immunohistochemical and genetic analyses are needed. J. Surg. Oncol. 2016;114:211-215. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…As previously reported for CA cases [5], the tumor cells in our case focally lined the alveolar wall – with their copious mucin destroying the alveoli – or were found floating in the mucin. Our immunohistochemical results were similar to those of previous CA studies [1, 5].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As previously reported for CA cases [5], the tumor cells in our case focally lined the alveolar wall – with their copious mucin destroying the alveoli – or were found floating in the mucin. Our immunohistochemical results were similar to those of previous CA studies [1, 5].…”
Section: Discussionsupporting
confidence: 81%
“…As previously reported for CA cases [5], the tumor cells in our case focally lined the alveolar wall – with their copious mucin destroying the alveoli – or were found floating in the mucin. Our immunohistochemical results were similar to those of previous CA studies [1, 5]. As classified by Rossi et al [1], there are two types of CA: (1) the goblet cell type and (2) the signet ring type, which are positive and negative for CDX2 and MUC2, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…[ 12 ] Focally preserved walls are lined by neoplastic epithelium in a single layer of tall, cuboidal to columnar, mucin-secreting cells, and admixed goblet cells. [ 11 12 13 ] The neoplastic mucinous cells show basally located small nuclei with inconspicuous nucleoli, lack of mitosis, and apically situated mucin as in our case; however, they have been noted with nuclear stratification, papillary epithelial projections, tufting, mild to moderate atypia, and occasional mitosis. [ 12 ] Tumors histologically consistent with colloid adenocarcinoma are difficult to distinguish from metastatic tumors with similar morphology.…”
Section: Discussionmentioning
confidence: 57%
“…Mucinous or colloid adenocarcinoma is an extremely rare subtype of lung adenocarcinoma and is characterized by pools of mucin-containing spaces with scant epithelium. [ 10 11 ] Previously, these have been designated under various terms, including mucinous cystadenoma, mucinous cystic tumor, multilocular cystic adenocarcinoma, and mucinous cystic tumor of borderline malignancy; however, in the most recent International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society classification, this terminology was discontinued and these tumors were included under the category of colloid adenocarcinoma. [ 2 ] Grossly, these tumors are well-circumscribed, intrapulmonary, lobulated and soft, with a central cavity filled with translucent mucus, ranging in size from 1 to >10 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The first case of colloid adenocarcinoma was reported by Graemes cook, et al in 1991 [6], since 76 cases were reported in the literature. There were 41 women and 35 men with extreme ages between 35 and 86 years and a mean of 63.7 [2,[4][5][6][7][8][9][10][11][12][13][14][15][16]. Most of patients were asymptomatic with the lesion incidently discovered on chest X-ray [8,11].…”
Section: Discussionmentioning
confidence: 99%